Comparison of electrical characteristics between AlGaN/GaN and lattice-matched InAlN/GaN heterostructure Schottky barrier diodes. (June 2016) - Ren, Jian; Yan, Dawei; Zhai, Yang; Mou, Wenjie; Gu, Xiaofeng
Abstract: Lattice-matched Pt/Au–In0.17 Al0.83 N/GaN hetreojunction Schottky barrier diodes (SBDs) with circular planar structure have been fabricated. The electrical characteristics of InAlN/GaN SBD, such as two-dimensional electron gas (2DEG) density, turn-on voltage, Schottky barrier height, reverse breakdown voltage and the forward current-transport mechanisms, are investigated and compared with those of a conventional AlGaN/GaN SBD. The results show that, despite the higher Schottky barrier height, more dislocations in InAlN layer causes a larger leakage current and lower reverse breakdown voltage than the AlGaN/GaN SBD. The emission microscopy images of past-breakdown device suggest that a horizontal premature breakdown behavior attributed to the large leakage current happens in the InAlN/GaN SBD, differing from the vertical breakdown in the AlGaN/GaN SBD. Highlights: We fabricate lattice-matched Pt/Au–In0.17 Al0.83 N/GaN SBDs. The electrical characteristics of InAlN/GaN SBDs are investigated by EMMI and CL. A horizontal premature breakdown behavior is observed in InAlN/GaN SBDs. The reason of large leakage current and low breakdown voltage is explained.